Language visibility in the public space: the linguistic landscape of Masvingo, Zimbabwe - Jenjekwa, Vincent (Taylor and Francis Group, 2022)
This article investigates the language situation in the public space in Masvingo Province, Zimbabwe, from a linguistic landscape point of view. The data consists of written information displayed on billboards, road signs and buildings. Data were also generated through in-depth interviews and documentary study. The theoretical underpinnings of the study are founded in the linguistic landscape and post-colonial theories. The study established the overwhelming dominance of English both in the cityscape and landscape. While Shona, one of the major indigenous languages of Zimbabwe, appears in a few instances in the form of proper names, most local languages are not part of the visible signs on roads, billboards and buildings in Masvingo. This gives English de facto status as the sole official language, regardless of the fact that the constitution of Zimbabwe officially recognises 15 indigenous languages in addition to English. This silencing of indigenous languages has serious implications for equity in language use in Zimbabwe. The study recommends equitable treatment of languages in the public space to ensure that the languages and cultures associated with all languages of Zimbabwe do not gradually die.